PENGARUH POLA PENGGERGAJIAN DAN SUDUT SAYAT TERHADAP RENDEMEN DAN PRODUKTIVITAS PENGGERGAJIAN KAYU NIBUNG (ONCOSPERMA TIGILLARIUM) - Osly Rachman; Dede Rohadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Nibung (Oncosperma tigillarium) is a member of palm family which has a good potential for utilization. An experiment to find out the best sawing pattern and hook angle of saw blade for better recovery and sawing productivity was conducted. Two sawing patterns (live sawing and sawing around) and two hook angles (20 and 27 degrees were applied).The results indicated that sawing around pattern produced higher recovery of hard and medium wood than live sawing as much as 8%, while the 27° of hook angle produced higher productivity than 20° angle as much as 0.30 m2/min.